Direct observation of disulfide isomerization in a single protein - Alegre-Cebollada, Jorge; Kosuri, Pallav; Rivas-Pardo, Jaime Andrés; Fernández, Julio M. (Nature chemistry, 2011)
Photochemical uncaging techniques use light to release active molecules from otherwise inert compounds. Here we expand this class of techniques by demonstrating the mechanical uncaging of a reactive species within a single protein. We proved this novel technique by capturing the regiospecific reaction between a thiol and a vicinal disulfide bond. We designed a protein that includes a caged cysteine and a buried disulfide. The mechanical unfolding of this protein in the presence of an external nucleophile frees the single reactive cysteine residue, which now can cleave the target disulfide via a nucleophilic attack on either one of its two sulfur atoms. This produces two different and competing reaction pathways. We used single-molecule force spectroscopy to monitor the cleavage of the disulfides, which extends the polypeptide by a magnitude unambiguously associated with each reaction pathway. This allowed us to measure, for the first time, the kinetics of disulfide-bond isomerization in a protein. Multiple redox reaction pathways exist in proteins containing several cysteines. A technique termed mechanical uncaging is now demonstrated, allowing the release of a single reactive cysteine within a protein and the unequivocal observation of subsequent thiol/disulfide exchanges. Mechanical uncaging of reactive groups is useful for studying chemical kinetics in a synchronized manner.